2023
DOI: 10.1186/s12904-023-01144-1
|View full text |Cite
|
Sign up to set email alerts
|

Muslim patients in the U.S. confronting challenges regarding end-of-life and palliative care: the experiences and roles of hospital chaplains

Abstract: Introduction Hospital chaplains aid patients confronting challenges related to palliative and end-of-life care, but relatively little is known about how chaplains view and respond to such needs among Muslim patients, and how well. Methods Telephone qualitative interviews of ~ 1 h each were conducted with 23 chaplains and analyzed. Results Both Muslim and non-Muslim chaplains raised issues concerning Is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In several in-depth qualitative research interview studies the author has conducted over several years on a variety of disorders, questions of “why me?” have often arisen. Other issues that emerged in these interviews have been reported elsewhere ( Klitzman, 1997 , 2008 ; 2012 , 2019 ; Klitzman et al, 2023 ). However, in these interviews, issues regarding “why me?” also frequently arose spontaneously, and data from these studies are thus brought together here for the first time to analyze in systematic ways how patients’ use the phrase “why me?“, what meanings it may have and what phenomena may be involved.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In several in-depth qualitative research interview studies the author has conducted over several years on a variety of disorders, questions of “why me?” have often arisen. Other issues that emerged in these interviews have been reported elsewhere ( Klitzman, 1997 , 2008 ; 2012 , 2019 ; Klitzman et al, 2023 ). However, in these interviews, issues regarding “why me?” also frequently arose spontaneously, and data from these studies are thus brought together here for the first time to analyze in systematic ways how patients’ use the phrase “why me?“, what meanings it may have and what phenomena may be involved.…”
Section: Introductionmentioning
confidence: 71%
“…This article draws on several qualitative research studies ( Klitzman, 1997 , 2008 ; 2012 , 2019 ; Klitzman et al, 2023 ) of how patients, including physicians when they develop serious disease, cope with various conditions, including HIV, diagnoses associated with genetic testing (e.g., breast cancer and Huntington’s disease [HD]) and infertility/in vitro fertilization (IVF), and hospital chaplains, supplemented by additional conversations with patients and providers. Methodological and other data from these studies have been reported elsewhere ( Klitzman, 1997 , 2008 ; 2012 , 2019 ; Klitzman et al, 2023 ). In brief, these studies explored participants’ views, experiences, challenges and decisions concerning the medical issues confronted, including ways of coping, to obtain “thick descriptions” ( Geertz, 1973 ).…”
Section: Methodsmentioning
confidence: 99%
“…Providing information about the available alternative therapies is part of informed consent and constitutes part of the respect for the patient’s autonomy. Recognition of the religious beliefs of the Muslim patient is a very important factor in the interaction between physician and patient to obtain informed consent for medical treatment [ 5 , 39 ]. Failure to respect religious sensitivities regarding the use of biological products such as materials from porcine sources can have serious consequences.…”
Section: Discussionmentioning
confidence: 99%
“…When no substitute can be used, patients, family members, guardians, and even religious leaders may be involved in the decision-making process [ 7 , 8 ]. It is highly recommended for hospitals to engage their local Muslim communities to create general guidelines and policies for that hospital so that those Muslims who do not agree with those guidelines or policies can take their patients to a different hospital if possible, and thus make timely and informed decisions [ 37 – 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation